2022
DOI: 10.1002/jcla.24760
|View full text |Cite
|
Sign up to set email alerts
|

LINC00511 aggravates the malignancy of lung adenocarcinoma through sponging microRNA miR‐4739 to regulate pyrroline‐5‐carboxylate reductase 1 expression

Abstract: Background Long non‐coding RNA LINC00511 is known to exacerbate lung adenocarcinoma (LUAD) progression. However, the specific mechanism by which LINC00511 affects LUAD progression has not been investigated as yet, and we aimed to elucidate the same in the present study. Methods The expression levels of LINC00511, microRNA miR‐4739, and pyrroline‐5‐carboxylate reductase 1 (PYCR1) were determined by quantitative reverse transcription PCR and Western blotting. The Cell Counting Kit‐8 and bromodeoxyuridine assays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
(88 reference statements)
0
1
0
Order By: Relevance
“…In the field of tumor malignancy, researchers have discovered numerous miRNA molecules and their corresponding target genes, which play significant roles in regulating chemoresistance [ 10 12 ]. Recent research has indicated that miR-4739 is downregulated in gastric cancer [ 13 ], prostate cancer [ 14 ], and lung adenocarcinoma [ 15 ], while it is upregulated in hepatocellular carcinoma [ 16 ]. In terms of functionality, increased expression of miR-4739 has been observed to inhibit the growth of esophageal squamous cell carcinoma (ESCC) cells by suppressing the expression of homeobox C10 [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the field of tumor malignancy, researchers have discovered numerous miRNA molecules and their corresponding target genes, which play significant roles in regulating chemoresistance [ 10 12 ]. Recent research has indicated that miR-4739 is downregulated in gastric cancer [ 13 ], prostate cancer [ 14 ], and lung adenocarcinoma [ 15 ], while it is upregulated in hepatocellular carcinoma [ 16 ]. In terms of functionality, increased expression of miR-4739 has been observed to inhibit the growth of esophageal squamous cell carcinoma (ESCC) cells by suppressing the expression of homeobox C10 [ 17 ].…”
Section: Introductionmentioning
confidence: 99%